Predictors of persistent symptoms after mRNA SARS-CoV-2 vaccine-related myocarditis (myovacc registry) - Schroth, Daniel; Garg, Ria; Bocova, Xhoi; Hansmann, Jochen; Haass, Markus; Yan, Andrew; Fernando, Carlos; Chacko, Binita; Oikonomou, Anastasia; White, James; Alhussein, Muhammad Mustafa; Giusca, Sorin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims: Epidemiological surveillance has raised safety concerns for mRNA SARS-CoV-2-vaccination-related myocarditis. We aimed to analyze epidemiological, clinical and imaging findings associated with clinical outcomes in these patients in an international multi-center registry (NCT05268458). Methods and Results: Patients with clinical and CMR diagnosis of acute myocarditis within 30 days after mRNA SARS-CoV-2 – vaccination were included from five centers in Canada and Germany between 05/21 – 01/22. Clinical follow-up on persistent symptoms was collected. We enrolled 59 patients (80 % males, mean age 29 years) with CMR-derived mild myocarditis (hs-Troponin-T 552 [249-1193] ng/l, CRP 28 [13-51] mg/l; LVEF 57 ± 7 %, LGE 3 [2-5] segments). Most common symptoms at baseline were chest pain (92 %) and dyspnea (37 %). Follow-up data from 50 patients showed overall symptomatic burden improvement. However, 12/50 patients (24%, 75% females, mean age 37 years) reported persisting symptoms (median interval 228 days) of chest pain (n=8/12, 67%), dyspnea (n=7/12, 58%), with increasing occurrence of fatigue (n=5/12, 42%) and palpitations (n=2/12, 17%). These patients had initial lower CRP, lower cardiac involvement in CMR, and fewer ECG changes. Significant predictors of persisting symptoms were female sex and dyspnea at initial presentation. Initial severity of myocarditis was not associated with persisting complaints. Conclusion: A relevant proportion of patients with mRNA SARS-CoV-2-vaccination-related myocarditis report persisting complaints. While young males are usually affected, patients with persisting symptoms were predominantly females and older. The severity of the initial cardiac involvement not predicting these symptoms may suggest an extracardiac origin.